2001
DOI: 10.1590/s1413-86702001000500004
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of Haemophilus influenzae at a Brazilian day care center

Abstract: Day care centers are a relatively new phenomenon in Brazil that bring together large numbers of young children susceptible to contagious diseases. Haemophilus influenzae (Hi) is an important infection in the age range of those attending day care centers. In the present study, the carriage rate of Haemophilus influenzae was identified in 38 day care attendees age 6 to 37 months, and 23 staff members, at a day care center in Ribeirão Preto-São Paulo, in 1997. To identify the carriers, two nasopharyngeal swabs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The most common colonizing biotypes were type II, I, V and III agreeing exactly with the result of a previous study (5). Recently, in a few studies in DCC in which Hi biotypes were reported, one in Brazil (5), one in France (35) where the most common biotypes for Hi were type II (62.2%), V (18.0%) and I (16.2%), and one in the USA (14), where the most common types were type II (37.0%), III (21.0%), I (13.0%), V (12.0%) matched the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common colonizing biotypes were type II, I, V and III agreeing exactly with the result of a previous study (5). Recently, in a few studies in DCC in which Hi biotypes were reported, one in Brazil (5), one in France (35) where the most common biotypes for Hi were type II (62.2%), V (18.0%) and I (16.2%), and one in the USA (14), where the most common types were type II (37.0%), III (21.0%), I (13.0%), V (12.0%) matched the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have documented Hi point prevalence colonization rates among various populations to range from 11 to 88% (3,5,9,16,20,31) and most likely depending on differences in the children's hygiene practices, behavior, or antibiotic use. In this study of nasopharyngeal cultures from children < 3 years old attending DCC in Ribeirão Preto-SP, the colonization rates are consistent with the variable rates reported.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal carriage of Hib is important in the transmission, pathogenesis and immunologic response [2]. The availability of conjugated capsular Hib vaccine has dramatically reduced the incidence of Hib-induced diseases in North America [3], Europe [4] and more recently in developing countries such as Brazil [5]. In unvaccinated populations, the invasive diseases caused by Hib particularly affect children under 6 years old [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…World Health Organization (WHO) reported that the deaths from bacterial meningitis in Europe, America, Africa and South East Asia was, 15,000, 18,000, 20,000 and 73,000 respectively 8 . Each year in USA the incidence of bacterial meningitis is 0.01% cases 9 . The incidence of bacterial meningitis varies from 0.022% to 0.266% in newborns, more common in developing countries 10 .…”
mentioning
confidence: 99%